Geometry-dependent lifetime of Interatomic coulombic decay using equation-of-motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2014)
Electronically excited atom or molecule in an environment can relax via transferring its excess energy to the neighboring atoms or molecules. The process is called Interatomic or Intermolecular coulombic decay (ICD). The ICD is a fast decay process in environment. Generally, the ICD mechanism predominates in weakly bound clusters. In this paper, we have applied the complex absorbing potential approach/equation-of-motion coupled cluster (CAP/EOMCCSD) method which is a combination of CAP and EOMCC approach to study the lifetime of ICD at various geometries of the molecules. We have applied this method to calculate the lifetime of ICD in Ne-X; X = Ne, Mg, Ar, systems. We compare our results with other theoretical and experimental results available in literature. (C) 2014 AIP Publishing LLC.